Comparison of anesthetic efficacy between oral infiltration with 4% articaine and inferior alveolar nerve block with 2% lidocaine: a prospective, randomized, double-blind clinical trial (Research, Society and Development, 2021)
For analgesia of posterior mandibular teeth, the most used anesthetic technique is the blockade of the inferior alveolar and lingual nerves, despite its relevant clinical failures. The aim of the present study was to compare the anesthetic efficacy of supraperiosteal infiltration with 4% articaine (INFILT) compared to inferior alveolar nerve block with 2% lidocaine (BNAI), both with 1:100,000 epinephrine, in lower posterior teeth. Sixty volunteers of both genders were selected, with indication for Black Class I or II restorations in mandibular posterior dental elements. The electric pulp tester device was used to evaluate the following parameters: pulp onset time (time from the end of the injection to the first non-sensing measurement), duration of the pulp anesthetic effect (time between the first and last non-sensing measurements) and anesthetic success (minimum of two consecutive measurements without sensitivity). Pain during the technique was measured using an 11-point boxed pain scale. The success rate presented by INFILT was higher than that of BNAI (p=0.0149). On the other hand, no significant differences were found with regard to latency time (p=0.4755), duration of pulpal anesthetic effect (p=0.1381) and pain on puncture and injection (p=0.9256). The rate of postoperative complications was 36.7% in both groups, all of which were classified as having low severity, ensuring clinical safety for the use of both techniques. Infiltration with articaine had a higher success rate compared to inferior alveolar nerve block with lidocaine. Once local anesthesia was achieved, there were no differences in the duration of effect between the two techniques.